Optimization of Security Coaching and Counseling by the Social Order Unit to Prevent Child Rapes in Grobogan Police Resort (Advances in Police Science Research Journal, 2024)
The increasing number of child rape cases in Grobogan has motivated this research to be done. Preemptive action such as security coaching and counseling is charged to the Social Order Unit to prevent child rapes, so the objective of the study is to optimize the implementation of security coaching and counseling by the Social Order Unit due to child rape prevention. Data in this qualitative research is accumulated through observations, interviews, and document studies. The Management Theory and SWOT Analysis Theory are used in this study. Based on the principles of Management Theory, the study identifies various issues either from the working system or the organizational resources. Specifically, the working system is not optimal due to insufficient planning, non-personnel competence-based organization, lack of electronic methods empowerment, lack of coordination with relevant agencies, and lack of supervision. In addition, here are the issues that are identified in organizational resources such as shortage of personnel quality and quantity, lack of target-oriented fund plans, lack of electronic methods empowerment, and inadequate facilities. Related to the elaboration above, The study recommends solutions to address these issues, including increasing personnel number and competence, improving the fund plans, empowering the electronic security coaching and counseling methods via social media, and improving the facilities. Furthermore, the study suggests several measures to optimize the Security and Safety Unit's technical aspects, such as consistent planning activities based on previous experiences, assigning tasks by the personnel-competence-based organization, coordination with the relevant agencies due to the child rapes coaching and counseling material, and evaluating the effectiveness of the program gradually by the forum group discussion methods.
Keywords: Optimalisasi; Bimbingan dan Penyuluhan; Unit Bintibsos; Satbinmas; Persetubuhan dan Pencabulan Anak; Anak; Grobogan